ANALISIS WACANA KOGNITIF PADA CERITA PENDEK KARYA PENDERITA GANGGUAN MENTAL DI FAM HEALTH INDONESIA - Istiqomah Putri Lushinta (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study is driven by the high prevalence of mental health disorders. It aims to explore the role of literary therapy through short story writing, particularly in the field of education. Using a descriptive qualitative method with Van Dijk’s cognitive discourse analysis, data were collected through observation and note-taking, involving two individuals with mental disorders from FAM Health Indonesia. The findings show that both subjects expressed emotional wounds through short story writing as a form of self-healing. Discourse analysis reveals attempts to manage stress through regular writing activities. It can be concluded that writing can serve as an effective therapeutic medium to reduce symptoms of depression and anxiety, while providing deeper insight into the healing process through creative literary expression. This study makes an important contribution to promoting writing activities as a means of addressing mental health challenges within educational institutions.